Safety and Efficacy of Bimekizumab in Patients With Active Psoriatic Arthritis: Three‐Year Results From a Phase IIb Randomized Controlled Trial and Its Open‐Label Extension Study. Issue 12 (18th November 2022) - Coates, Laura C.; McInnes, Iain B.; Merola, Joseph F.; Warren, Richard B.; Kavanaugh, Arthur; Gottlieb, Alice B.; Gossec, Laure; Assudani, Deepak; Bajracharya, Rajan; Coarse, Jason; Ink, Barbara; Ritchlin, Christopher T.
Abstract : Objective: To assess the long‐term safety, tolerability, and efficacy of bimekizumab in active psoriatic arthritis (PsA). Methods: Adult patients with active PsA who completed the double‐ and dose‐blind periods of the BE ACTIVE randomized controlled trial were eligible to enroll in the open‐label extension (OLE) study at week 48, after which patients received 160 mg of bimekizumab every 4 weeks. Safety and efficacy results are presented through 152 weeks. Results: At week 152, 161 of 206 patients (78.2%) remained in the study. From weeks 0–152, 184 of 206 patients experienced ≥1 treatment‐emergent adverse event (126.4 per 100 patient‐years). The most frequent events were nasopharyngitis (7.6 per 100 patient‐years), upper respiratory tract infection (6.8 per 100 patient‐years), bronchitis (3.5 per 100 patient‐years), and oral candidiasis (3.5 per 100 patient‐years). Additionally, 47 of 206 patients had mild to moderate localized fungal infections (9.7 per 100 patient‐years), including 24 of 206 patients who had Candida infections (4.6 per 100 patient years) and 19 of 206 patients who had oral candidiasis (3.5 per 100 patient years). Four patients had serious infections (0.7 per 100 patient‐years); there were no reported cases of active tuberculosis, adjudicated major adverse cardiac events, or deaths. Efficacy demonstrated at week 48 was sustained in the OLE study. At week 152, nonresponder imputation analysis showed that 52.9% of patients (69.4% of observed cases) achieved the American College of Rheumatology criteria for 50% improvement, 57.7% (73.8% of observed cases) achieved 100% skin clearance per the Psoriasis Area and Severity Index, and 51.5% (67.5% of observed cases) achieved minimal disease activity. Patients also maintained improvements in pain, physical function, and health‐related quality of life. Conclusion: The safety profile of bimekizumab was consistent with previous reports, with no new safety signals identified. Sustained joint and efficacy responses were observed over 3 years. Abstract : Video Abstract